Some features of stress markers for postoperative management of infants with urgent surgical pathology - Kondeti, Dhaneesh (Запорізький державний медичний університет, 2018)
Relevance of the Topic. In recent years, interest in the problem of postoperative pain and methods of combating it has increased significantly, due to the emergence of modern effective analgesia and awareness of the role of adequate anesthesia in postoperative rehabilitation of patients, especially high risk. Adequate postoperative analgesia is the main condition for the 70 implementation of the program of active post-operative rehabilitation. Recent epidemiological studies have found a paradoxical fact: the quality of postoperative pain relief in the XXI century is not rising, but, on the contrary, decreases. Despite the attention to this problem and the development of new methods for its solution, at least 35% of patients undergoing planned and emergency surgical interventions suffer from post-operative pain. Studies of recent years on perioperative intensive care, including postoperative anesthesia, have the children of the first year of life ambiguous and in some cases controversial. The purpose of the study is to study the markers of stress in children of the first year of life using different methods of analgesia.
Keywords: тези доповідей